The association between dietary protein intake and colorectal cancer risk: a meta-analysis - Lai, Renxu (World J Surg Oncol, 2017)
BACKGROUND: Association between dietary protein intake and colorectal cancer risk has not been fully quantified, while the results were controversial. This study aimed to evaluate the role of protein intake in the development of colorectal cancer. METHODS: PUBMED and EMBASE were searched up to December 2016. Two independent reviewers independently extracted data from eligible studies. Relative risk (RR) with 95% confidence intervals (CI) was pooled using random-effects model to estimate the result. Besides, publication bias and sensitivity analysis were conducted. RESULTS: Thirteen articles involving 21 studies comprising 8187 cases were included in this report. The pooled RR of colorectal cancer was 1.006 (95% CI = 0.857–1.179) indicating that there is no significant association between dietary protein intake and colorectal cancer risk. Furthermore, the pooled RRs for colon cancer and rectum cancer were 1.135(95% CI = 0.871–1.480) and 0.773(95% CI = 0.538–1.111), respectively, with the highest category of dietary protein intake. The association was not significant either in subgroup analysis of study design, protein type (animal protein or vegetable protein), sex, and or geographic locations. CONCLUSIONS: The present study indicated that the highest category compared to the lowest category of protein intake had no significant association on colorectal cancer risk. Dose-response analysis was not conducted due to limited information provided. Therefore, more studies with large cases and participants as well as detailed amounts of dietary protein intake are wanted to confirm this result. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12957-017-1241-1) contains supplementary material, which is available to authorized users.